Mentoring approach in learning fundamentals of islamic banking / Noor Saliza Zainal ...[et al.]. - Zainal, Noor Saliza; Mustafa @ Busu, Zanirah; Mat Jusoh, Nor Asmira; Awang @ Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah (2019)
This paper reviews the mentoring approach and its application at the learning institutions. Basically, mentoring approach is defined as a teaching method which involves a transfer of wisdom, where the mentor or coach provides advice or direction, probably based on their experience and expertise. Practically, often one selected student in the group is assigned to conduct learning relationship for understanding to other students. Currently, many courses taught at the universities are based on the traditional approach of teaching and learning. But, since there are many topics to be delivered for each course, some students might have problems in understanding each topic in depth. In addition to that, the lecturers also might not have enough time to clarify every topic thoroughly in class. Due to this problem, the group propose a mentoring approach as a supplementary approach of learning at the universities. In this study, we examine the perceptions on mentoring approach in learning of Fundamentals of Islamic Banking (CTU351) amongst the students at Universiti Teknologi MARA Kelantan, Machang campus. The objectives of this study have twofold. First, to determine the difference in mean perception on mentoring approach in learning Fundamentals of Islamic Banking across selected students' profiles. Secondly is to identify the factors affecting the perception on learning of Fundamentals of Islamic Banking. The results of the study show that many students do not have Mentor during their studies. Next, the study also found that their perceptions on mentoring approach do not significantly differ across gender, accommodation and mentor. Lastly, the results also prove that there is a positive correlation between Classroom with Outside Classroom and Surroundings in determining the learning of Fundamentals of Islamic Banking.